Fis Phenomenon in 3-Year-Old Child: Fis Phenomenon in 3-Year-Old Child - Desi Asnita (Program Studi Sastra Inggris Fakultas Ilmu Budaya Universitas Halu Oleo, 2017)
The aims of this research were: 1. to investigate more deeply about the fis phenomenon a child aged 3 year, 2. to fis phenomenon described in a 3-year-old child. The data of this research was taken Adelia Nur Febriyana from Jln. Jend A H Nasution. Lrg, Maleo. Kelurahan Kambu. Kota Kendari. Sulawesi Renggara. This study applied qualitative descriptive method. The techniques for collecting the data were observation, recording, and note. Based on the data analysis, the result show that Adelia Nur Febriyana had Fis Phenomenon. Where in pronounces the phoneme /R/ into /L/, the phoneme /S/ becomes /C/ or /T/ and sometimes removes the phoneme /k/ at the end of the word and the phoneme /h/ at the beginning of the word. The role of parents is very important in the development of children's language. Several factors that can affect a child's language development include family factors or the child's environment, in addition to supporting factors for children's language development, there are also inhibiting factors, namely the lack of perfect articulation tools so that they have obstacles but can be understood which have the same meaning and purpose. The research is still open for research on children's language acquisition, especially on further aspects of the fis phenomenon because there is still a lot that can be studied from children's language acquisition. Keywords: Language Acquisition, Fis Phenomenon, phoneme